The bases of conservation of spiritual values of the foreign Kazakhs in conditions of globalization (Journal of Philosophy Culture and Political Science, 2019)
It is considered in the article the bases of conservation of spiritual values of the Kazakhs abroad in conditions of globalization, the project of their self-development in the following years. The author also analyzed the leading role of Kazakh intelligentsia in the formong of national idea of the Kazakhs abroad. The author stresses that at the time the new Kazakhs are dissimilated all around the world and that the process of assimilation has gorgeous size not only among foreign Kazakhs. Keywords: globalization, cultural wealth, world civilization, national idea, consciousness.